Global Financial Stability Report, September 2003 : Market Developments and Issues. (Global Financial Stability Report; Global Financial Stability Report ;, 2003)
This September 2003 issue of the Global Financial Stability Report highlights that since March 2003, further progress has been made in addressing the lingering effects of the bursting of the equity price bubble. Household and corporate balance sheets have continued to improve gradually and corporate default levels have declined. Companies in mature markets have cut costs, enhancing their ability to cope with slower growth and other potential difficulties. Corporations-particularly in the United States-have made good progress in their financial consolidation efforts and are in a better financial position to increase investment spending.